Engaging Modern Muslims with Their Prophet: The Challenge of Contemporary Sīra Writing in the Thought of al-Azhar Scholar ʿAbd al-Ḥalīm Maḥmūd (1910-1978) - Vimercati Sanseverino, Ruggero (Arabica, 2023)
In contemporary Egypt, the secularization of discourses and practices raises a fundamental challenge to sīra writing concerning its vocation to make the founding narrative and the religious ideals of Islam comprehensible and meaningful to contemporary Muslims. Arguing that the Muslim community’s image of the Prophet does indeed both affect and reflect its religious and spiritual condition, the known Egyptian intellectual and former rector of al-Azhar, ʿAbd al-Ḥalīm Maḥmūd (1910-1978) holds the appearance of de-theologized forms of sīra writing as a symptom of a profound crisis of Islamic intellectuality. Against this background, his prophetological considerations seek to show that this challenge can only be overcome by a sīra writing that engages the audience in a personal and spiritual relationship with the Prophet.